Responsive 3D printed microstructures based on collagen folding and unfolding [data] - Mainik, Philipp; Aponte-Santamaria, Camilo; Fladung, Magdalena; Curticean, Ernest Ronald; Wacker, Irene; Hofhaus, Götz; Bastmeyer, Martin; Schröder, Rasmus R.; Gräter, Frauke; Blasco, Eva (Universität, 2024)
Mimicking extracellular matrices holds great potential for tissue engineering in biological and biomedical applications. A key compound for mechanical stability of these matrices is collagen, which also plays an important role in many intra- and intercellular processes. Two-photon 3D laser printing offers structuring of these matrices with subcellular resolution. So far, efforts on 3D microprinting of collagen have been limited to simple geometries and customized set-ups. Herein, we present an easily accessible approach using a collagen type I methacrylamide (ColMA) ink system which can be stored at room temperature and be precisely printed using a commercial two-photon 3D laser printer. The formulation and printing parameters are carefully optimized enabling the manufacturing of defined 3D microstructures. Furthermore, these printed microstructures show a fully reversible response upon heating and cooling in multiple cycles, indicating successful collagen folding and unfolding. This experimental observation has been supported by molecular dynamics simulations. Thus, our study opens new perspectives for designing new responsive biomaterials for 4D (micro)printing.
Gefördert durch: DFG Excellence Cluster “3D Matter Made to Order”: EXC-2082/1-390761711; Carl Zeiss Foundation: FocusHEiKA; Klaus Tschira Foundation; DFG grant: INST 35/1597-1 FUGG; DFG grant: INST 35/1503-1 FUGG
Gesehen am 27.11.2024
Keywords: Forschungsdaten; Datenbank